Kebijakan Jepang di Kawasan Asia Tenggara melalui Penandatanganan “Joint Declaration on AJCEP” di Era Kepemimpinan Junichiro Koizumi - Fitri, Nafira; Sushanti, S.S., M.Si., Sukma; Kawitri Resen, S.IP., M.A, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRAK This paper found that the making of Japanese foreign policy related to trade sector in Southeast Asia in the era of the leadership of Junichiro Koizumi. This topic is interesting, because until the mid-1990s, Japan committed to making the policy of multilateralism and reject the free trade agreements, because they assume the free trade agreement is not in accordance with the GATT / WTO. But in the era of Junichiro Koizumi changed the emphasis of economic cooperation to "act together and move forward together" with ASEAN and establish the ASEAN-Japan Comprehensive Economic Partnership (AJCEP) as the beginning of the establishment for the Free Trade Agreement. In this paper the author will examine the making of Japanese foreign policy-related trade in Southeast Asia in the era of the leadership of Junichiro Koizumi. With a locus of time in the 1998-2002, after Asian crisis in 1997 and the signing of the "Joint Declaration on the ASEAN-Japan Comprehensive Economic Partnership". This paper will explorate using Model II: Organizational Process by Graham T. Allison with the initial assumption that the change of foreign policy in the economic field in Japan is the result of the government organization in Japan which is influenced by external factors at that time and the list options which produced by the organization. Keyword: AJCEP, Junichiro Koizumi, the Asian Crisis, Free Trade Agreement